Turner syndrome with Xp deletions and rare endometrial abnormalities: A case report. Issue 46 (19th November 2021) - Liang, Lei; Mei, Libin; Shi, Yingying; Huang, Lingling; Su, Zhiying; Zeng, Yu; Gao, Haijie; He, Xuemei; Huang, Hui; Huang, Yanru; Li, Ping; Chen, Jing
Abstract: Rationale: Turner syndrome (TS) is a genetic disorder associated with abnormalities of the X chromosome related to ovarian function, but whether it is associated with endometrial abnormalities is still not clear. Patient concerns: We report the case of a 26-year-old Han Chinese woman with TS and Xp11.2 deletion, presenting with short final stature, ovarian hypofunction, unexplained cystic dilatation of the entire endometrium, and endometrial thickening. Diagnoses: The patient was diagnosed with chromosome Xp11.2 deletion through cytogenetic analysis and ultrasonic and endometrial pathology. Interventions: The patient was treated with conventional in vitro fertilization preimplantation genetic testing for 1 cycle. Outcomes: Cytogenetic examination showed karyotype 45, X, del (X) del (p11, 2). Ultrasonic examination showed uneven endometrium thickness and a full-stage cystic dilation echo. After 1 cycle of in vitro fertilization treatment, 4 eggs were obtained without forming an available embryo. Lessons: To our knowledge, the present case is the first report of a patient with TS with Xp deletions and ultrasound imaging endometrial abnormalities. Our findings expand the phenotypic spectrum of TS and may provide a reference for other clinicians.